TRANSFORMASI PEMBELAJARAN AGAMA HINDU MELALUI METODE SMART - Purnawati, Ni Komang; Rudiarta, I Wayan (Padma Sari: Jurnal Ilmu Pendidikan, 2025)
This research is motivated by the issues in Hindu religious education at Senior High School 4 Mataram, which still relies on conventional methods such as lectures and note-taking. These methods create a monotonous learning environment and fail to holistically develop students' character and spirituality. To address this issue, the study adopts the SMART Method (Sattva, Maitri, Adhyayana, Rasa, and Tapas) as an innovative learning approach that integrates the noble values of Hindu teachings with a holistic instructional strategy that engages cognitive, emotional, and spiritual dimensions. The research employs a descriptive qualitative approach, with data collection techniques including direct observation of the learning process, document analysis (such as syllabi, lesson plans, and evaluation results), and literature reviews to reinforce the theoretical foundation. The data were systematically analyzed through reduction, narrative presentation, and conclusion drawing based on patterns observed throughout the learning process. The findings indicate that the application of the SMART Method successfully fosters a more dynamic and meaningful learning atmosphere, enhances student engagement, and cultivates discipline, empathy, and deep spiritual awareness. Therefore, the SMART Method not only improves cognitive aspects but also strengthens the moral and social dimensions of students, making Hindu religious education a comprehensive self-transformation process that aligns with contemporary educational needs.